Biofloc technology as a promising tool to improve aquaculture production - Mohammad Hossein Khanjani; Moslem Sharifinia (Reviews in Aquaculture, 2020)
Given that the expansion of the aquaculture industry is associated with increased environmental impact and its strong dependence on fishmeal in the diet, the use of biofloc technology can reduce these problems. This technology absorbs inorganic nitrogen from aquaculture wastewater and improves water quality as well as produces microbial protein that is directly used as a suitable feed supplement for aquatic animals. Furthermore, this technology reduces the feed conversion ratio and subsequent production cost. Biofloc is available to aquatic animals throughout the day and provides the necessary nutrients, fatty acids and minerals. Biofloc along with formulated diets provides a complete food chain for aquatic animals’ growth and thus improves growth performance. Since feed constitutes a major part of the aquaculture cost, having accurate information about biofloc system in aquatic animals’ nutrition can be beneficial and helpful. Compared to traditional aquaculture techniques, biofloc technology provides a more sustainable approach with minimal water exchange along with reduced feed intake and transforms it into a low‐cost sustainable technology for sustainable aquaculture development. Overall, this study highlights the significance of developing biofloc technology to improve aquaculture production and could be an alternative system for cultivation of important commercial species in aquaculture.